2015
DOI: 10.1016/j.conbuildmat.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of reactive magnesia and sodium carbonate-activated fly ash/slag paste blends

Abstract: A system of alkali-activated fly ash (FA)/slag (AAFS) mixtures as a clinkerless cement was investigated with different dosages of Na 2 CO 3 , as a sustainable activator. The effect of incorporating various proportions of reactive magnesia (MgO) was also examined. Mechanical, mineralogical, and microstructural characterisation of the cement pastes was carried out using the unconfined compressive strength, X-ray diffraction, thermogravimetric analysis, infrared spectroscopy and scanning electron microscopy. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(63 citation statements)
references
References 41 publications
7
52
2
2
Order By: Relevance
“…Gaylussite (Na 2 Ca(CO 3 ) 2 Á5H 2 O) is a secondary reaction product of sodium carbonate activation and will be entirely transferred to more stable products (Eq. 1) [4,28]. As shown in Table 4, the amounts of calcite of all samples after a long period of curing are remaining at the same levels, indicating that the released CO 3 2-anions from gaylussite are transferred to other phases such as hydrotalcite-like phases.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Gaylussite (Na 2 Ca(CO 3 ) 2 Á5H 2 O) is a secondary reaction product of sodium carbonate activation and will be entirely transferred to more stable products (Eq. 1) [4,28]. As shown in Table 4, the amounts of calcite of all samples after a long period of curing are remaining at the same levels, indicating that the released CO 3 2-anions from gaylussite are transferred to other phases such as hydrotalcite-like phases.…”
Section: Discussionmentioning
confidence: 63%
“…It is reasonable to assume that the formation of natron is mainly caused by the lack of sufficient ions from slag particles such as Mg 2? and Al 3? to react with the released CO 3 2-anions from the conversion of gaylussite. Abdalqader et al [28] characterized the reaction products of sodium carbonate activated slag-fly ash blenders and reported that no new phase was formed with up to 25% addition of fly ash or difficult to be identified. While, in the present study, the presence of LP in the mixture is observed to be involved in the chemical reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the activators applied, CO 3 2-and SO 4 2-anions are also identified in the samples as shown in the spectra. The peaks centred at about 1410 and 1493 cm -1 are assigned to be the vibrations of v 3 [CO 3 2-], which can be calcium carbonate or hydrotalcite [40][41][42]. A small peak at this position was also observed in the mixture activated by pure sodium sulfate, possibly due to a slight carbonation or originated from slags.…”
Section: Reaction Products Characterizationmentioning
confidence: 92%